Uma análise do discurso publicitário do Conselho Nacional de Justiça - Lodi, Marluce Dantas de Freitas (2011)
The present work analyzes how the National Council of Justice (CNJ) builds its corporate image along with citizens. Public Administration has become more sensible to the external environment and, in some countries, citizens have determined how the service should be provided. Treated as a customer, the citizen is more aware and demanding of their rights, seeking quick answers to your needs and greater efficiency in service delivery, controlling and charging solution more actively. Therefore, one of CNJ's clear concerns is related to changing the judiciary's image and since 2008 CNJ has released publicity campaigns for this purpose. Aiming to analyze the forms of communication used by the judiciary, official advertisements used by CNJ were analyzed and interpreted. To guide the advertisements analysis and building process of the judiciary‟s corporate image, the researcher used the method of advertising discourse analysis as proposed by Pinto (2002). Throughout methodological procedures section, exhibition function (discourse universe construction), interaction (establishment of socio-cultural ties) and seduction (distribution of positive and negative affects) are showed and discussed to serve as subject for understanding the ways of building publicity discourses that are present in pieces of the CNJ. The relevance of this work lies in the fact that it is a very important topic for public administration and the Judiciary, which is institutional communication and interactivity between justice and society.